Association of Methylenetetrahydrofolate Reductase (MTHFR 677C>T and 1298A>C) Polymorphisms and Haplotypes with Silent Brain Infarction and Homocysteine Levels in a Korean Population - Han, In Bo (Yonsei University College of Medicine, 2010)
PURPOSE: Methylenetetrahydrofolate reductase (MTHFR) is the main regulatory enzyme for homocysteine metabolism. In the present study, we evaluated whether the MTHFR 677C>T and 1298A>C gene polymorphisms are associated with SBI and plasma homocysteine concentration in a Korean population. MATERIALS AND METHODS: We enrolled 264 patients with SBI and 234 healthy controls in South Korea. Fasting plasma total homocysteine (tHcy) concentrations were measured, and genotype analysis of the MTHFR gene was carried out. RESULTS: The plasma tHcy levels were significantly higher in patients with SBI than in healthy controls. Despite a significant association between the MTHFR 677TT genotype and hyperhomocysteinemia, the MTHFR 677C>T genotypes did not appear to influence susceptibility to SBI. However, odds ratios of the 1298AC and 1298AC + CC genotypes for the 1298AA genotype were significantly different between SBI patients and normal controls. The frequencies of 677C-1298A and 677C-1298C haplotypes were significantly higher in the SBI group than in the control group. CONCLUSION: This study demonstrates that the MTHFR 1298A>C polymorphism is a risk factor for SBI in a Korean population. The genotypes of 677C>T and 1298A>C polymorphisms interact additively, and increase the risk of SBI in Korean subjects.